2012
DOI: 10.1080/15459624.2012.667349
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Mortality Study of Roofing Granule Mine and Mill Workers. Part II. Epidemiologic Analysis, 1945–2004

Abstract: The mortality of 2650 employees (93.4% males) in the mine and mill production of roofing granules at four plants was examined between 1945 and 2004. Hypotheses focused on diseases associated with exposure to silica: nonmalignant respiratory disease, lung cancer, and nonmalignant renal disease. Study eligibility required ≥ 1 year of employment by 2000. Work history and vital status were followed through 2004 with < 1% lost to follow-up. Industrial hygiene sampling data (1871 sampling measurements over a 32-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…MacDonald et al [7] conducted a mortality study and showed that quartz exposure in North American industrial sandblasting workers increased mortality due to lung cancer, but not due to chronic renal disorders or renal cancer. Olsen et al [8] also researched the mortality of silica-exposed workers at 4 plants and demonstrated that 16 workers (2%) had died as a result of nonmalignant renal disease among 772 total deaths. In the same study, 50 deaths (6%) were attributed to nonmalignant respiratory system disease, and a total of 77 (1%) lung cancer deaths.…”
Section: Discussionmentioning
confidence: 99%
“…MacDonald et al [7] conducted a mortality study and showed that quartz exposure in North American industrial sandblasting workers increased mortality due to lung cancer, but not due to chronic renal disorders or renal cancer. Olsen et al [8] also researched the mortality of silica-exposed workers at 4 plants and demonstrated that 16 workers (2%) had died as a result of nonmalignant renal disease among 772 total deaths. In the same study, 50 deaths (6%) were attributed to nonmalignant respiratory system disease, and a total of 77 (1%) lung cancer deaths.…”
Section: Discussionmentioning
confidence: 99%
“…These estimates were then used in an exposure-response analysis comparing the cumulative exposures with the probability of developing occupational disease, such as silicosis and exposure-related lung cancer. (7) The process of developing a JEM included the following steps: A team of investigators was assembled to locate, acquire, review, and summarize the available exposure data for the four plants. The team consisted of the lead investigators, consultants, and industrial hygienists with plant experience.…”
Section: Methodsmentioning
confidence: 99%
“…Using the JEM, cumulative RCS exposures were calculated for each of 2650 workers who met the eligibility criteria. (7) The earliest RCS measurements were collected in 1972, yet estimates of plant and job specific mean exposures were required for those workers with job histories extending back to 1961, 1948, 1947, and 1945 for the Belle Mead, Corona, Little Rock, and Wausau cohorts, respectively. After reviewing the mine and mill histories, the study team determined that the mine and mill operations were relatively stable until the 1970s.…”
Section: Job Exposure Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also found that cardiovascular disease is the leading cause of death in silicosis patients of coal mines (Landen et al 2011;Morozova 2012). The positive relationship between occupational silica exposure and chronic kidney disease [standard mortality ratio (SMR) = 1.76, 95 % confidence interval (CI) 1.01-2.86] was observed by Olsen et al (2012) in an epidemiological study of 2,650 participants. Vupputuri et al (2012) demonstrated that silica exposure was associated with a 40 % increased risk of chronic kidney disease compared with non-exposed controls after adjusting for potential confounders.…”
Section: Introductionmentioning
confidence: 99%